Malaysian management practices : an empirical study - Hassan, Arif; Mohd. Israil, Khaliq Ahmad (Leeds Publications, 2001)
Norms of justice employed in the allocation of organizational resources and fairness of the process have attracted a large number of social and organizational researchers. The subject had been discussed from several economic, ethical, and legal….